2007
DOI: 10.1038/sj.ejcn.1602951
|View full text |Cite
|
Sign up to set email alerts
|

Dietary carbohydrates, glycemic load and serum high-density lipoprotein cholesterol concentrations among South Indian adults

Abstract: Objective: To examine the relationship between dietary carbohydrates, glycemic load and high-density lipoprotein cholesterol (HDL-C) concentrations in Asian Indians, a high-risk group for diabetes and premature coronary artery disease. Subjects/methods: The study population comprised of 2043 individuals aged X20 years randomly selected from Chennai Urban Rural Epidemiological Study (CURES), an ongoing population-based study on a representative population of Chennai (formerly Madras) city in southern India. Par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
26
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 34 publications
3
26
2
Order By: Relevance
“…Randomized and metabolic studies have shown that white rice and refined wheat flour products increase fasting triglyceride levels and reduce HDL-C concentrations [33,34]. Our current results are in agreement with our previous finding that a higher dietary glycemic load intake was associated with lower HDL-C levels [35]. Consistent with another cross-sectional study conducted among older adults [16], we also found that higher refined grains intake was associated with higher fasting glucose concentration.…”
Section: Discussionsupporting
confidence: 94%
“…Randomized and metabolic studies have shown that white rice and refined wheat flour products increase fasting triglyceride levels and reduce HDL-C concentrations [33,34]. Our current results are in agreement with our previous finding that a higher dietary glycemic load intake was associated with lower HDL-C levels [35]. Consistent with another cross-sectional study conducted among older adults [16], we also found that higher refined grains intake was associated with higher fasting glucose concentration.…”
Section: Discussionsupporting
confidence: 94%
“…This was accompanied by lower ApoA1 levels. This predilection of South Asians to have lower HDL-C levels is well known (2), and has been attributed to the higher prevalence of insulin resistance and related metabolic abnormalities, which may be the consequence of a combination of genetic predisposition, physical inactivity, and a high-carbohydrate diet (2,9,10). By contrast, among other Asian subgroups, HDL-C levels were higher and similar to levels in non-Asians.…”
Section: Figure 3 Ors For Risk Of First Ami With Increasing Hdl-c Levcontrasting
confidence: 53%
“…), who may differ in their lipid profiles (3). These differences may be the result of both genetic and environmental factors (high-carbohydrate diets, reduced physical activity, and so on) (9,10).…”
mentioning
confidence: 97%
“…The ratios of TC to HDL and LDL to HDL are recognized as better indicators for CVD risk [32,33], and total cholesterol alone may not be adequate for predicting MI candidates [34]. In the case of triglycerides, variations derived from dietary supplements [35,36] and regions were found [37]. In addition, the alteration of the lipid profile due to gender differences was observed in healthy participants and patients with metabolic disease, and the levels of HDL and triglycerides were higher in healthy women than men [38,39].…”
Section: Discussionmentioning
confidence: 99%